Lessons for the Urban Century : Decentralized Infrastructure Finance in the World Bank - Clarke Annez, Patricia (Washington, DC : World Bank, 2012)
This book takes a look at the past to gain insights for the future. Nearly 30 years ago, when the world urban population was only about half of the 3 billion that it is today, when most Less Developed Countries (LDCs) were primarily rural, and before the wave of decentralization of the 1980s and 1990s, the World Bank developed an instrument with great potential. The key characteristics of this instrument, the Urban Infrastructure Fund (UIF), are several. It provides finance for an array of urban services, not just one sector, such as water and sanitation, leaving flexibility for local beneficiaries to set their priorities. UIF projects operate in more than one city. Perhaps the most important distinctive feature is that these projects use local institutions to do the work of identifying, appraising and channeling finance to subnational entities (municipalities, local utilities, or community groups) on behalf of the World Bank. This arrangement makes it feasible to reach beyond the major capitals or business centers such as Chongqing, Mumbai, or Sao Paulo, or even regional capitals, to fund much smaller subprojects, suited to the needs and capacities of smaller cities and towns, because local agents are tasked with identifying and appraising these projects. Delegating these functions makes it practicable not only for a large International Financial Institution (IFI) such as the World Bank but also for national governments to reach small municipalities. Providing support to large numbers of municipalities with relatively small investment needs is a complex task, but it is fundamental to scaling up beyond small pilot projects to programs improving urban services countrywide.